The contribution and interactive relationship of tourism industry development and technological innovation to the informatization level: Based on the context of low-carbon development - Zimeng, Guo; Wei, Yang; Qiuxia, Chen; Xiaoting, Huang (Frontiers in Environmental Science, 2023)
Informatization is a new economic form arising from a new round of technological and industrial changes. Information technology has been used to promote the integrated development of the tourism industry and propel technological innovation, which will help accelerate the achievement of the strategic goals of carbon emission peaking and carbon neutrality. China's informatization level has improved to a certain extent due to the concentration of capital and technological innovation brought about by the government-led model, and also owing to the consumer dynamics released by the industry-side reform. This study constructs a panel vector auto-regression model to investigate the impact of tourism industry development and technological innovation on informatization based on Chinese provincial statistics from 2010 to 2019. This study adopts the entropy method, Monte Carlo simulation, variance decomposition, and pulse response to investigate the impact, characteristics, and trends of their interactions. The results indicate that: first, tourism industry development, technological innovation, and informatization all experience inertia development and have self-reinforcing mechanisms during the research period. Second, tourism industry development and technological innovation have a significantly positive impact on the enhancement of informatization, and their influence presents a trend, from upward to downward. Third, tourism industry development has a positive impact on technological innovation, and the response trend presents a curve approximately inverted U-shape. Fourth, from the results of variance decomposition, the contribution of technological innovation to the improvement of informatization level increases rapidly and reaches 18.5% and then levels off. The contribution rate of tourism industry development to the improvement of informatization level gradually rises and reaches 5.1%, finally tending to be stable. The research results provide a reference basis for the government and related industrial sectors in how to effectively facilitate the development of informatization in the context of the low-carbon economy.